UPAYA PENINGKATAN KEMAMPUAN MENARI TARI TOPENG GUNUNGSARI PADA MAHASISWA JURUSAN PENDIDIKAN SENI TARI DENGAN PENDEKATAN APRESIASI SENI DAN LATIHAN SECARA RUTIN - Herlinah - (FBS UNY, 2007)
The research was purposed to make efforts to improve Dance Education Department student dancing abilities of Topeng Gunungsari Dance by Art Appreciation method and practiced routinely . The research used design models which were developed by Kemmis Mc. Taggart consisted of four components included; planning, action, observation, and reflection. The researchers planned and established action types which would be done, that were; student practiced together by masks, and watched a Topeng Gunungsari Dance performance by video recording routinely. The research result of dance studying was that by the practiced and watched a Topeng Gunungsari Dance video recording routinely could improve dancing abilities of Topeng Gunungsari dance. Key words: dancing ability, art appreciation, routine practice.